TREATMENT OF ALLERGIC RHINITIS IN CHILDREN: SELECTION OF ANTIHISTAMINE DRUG AND NECESSITY OF FURTHER INVESTIGATIONS - A. V. Karaulov (Вопросы современной педиатрии)
This literature review contains analysis of research results on treatment of allergic rhinitis in children according to the evidence-based medicine. Oral and intranasal antihistamine drugs along with intranasal steroids are the first-line drugs for treatment of allergic rhinitis, although the latter are more efficient in suppression of nasal stuffiness. First- and second-generation antihistamine agents used nowadays in medical practice are discussed in the article. The advantages of non-sedative 2d-genereation antihistamine drugs, especially so called active metabolites (fexofenadine, cetirizine, levocetirizine, desloratadine) are emphasized. The data on loratadine and desloratadine as ones of the most effective drugs in childhood allergic rhinitis are shown in detail. The possible directions for the further investigations in order to provide effective control over allergic inflammation in children resistant to medicinal agents are discussed.